2023
DOI: 10.1002/wer.10902
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic and total dissolved solids removal using antibacterial/antifouling nanofiltration membranes modified by functionalized graphene oxide and copper ferrodioxide

Abstract: The intrinsic hydrophilicity of metal compounds, such as copper ferrite (CuFe2O4), and organic compounds, including graphene oxide (GO) and triethylenetetramine (TETA), make them promising adsorbents for heavy metals removal. The presence of lone pairs in these compounds is observed in modified polyethersulfone membranes used for the separation of arsenic (As) and total dissolved solids (TDS), including mono and divalent salts from aqueous solutions. The objective of this study was to investigate the performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…GO-TETA-CuFe 2 O 4 membranes demonstrated significantly higher resistance to fouling than the PES NF membranes. The hydraulic reversibility test showed that the total resistance changes from 6.78 × 10 12 m −1 to 2.07 × 10 12 m −1 [135].…”
Section: Stability-antifouling Properties Of 2d Materials Nf Membranementioning
confidence: 99%
“…GO-TETA-CuFe 2 O 4 membranes demonstrated significantly higher resistance to fouling than the PES NF membranes. The hydraulic reversibility test showed that the total resistance changes from 6.78 × 10 12 m −1 to 2.07 × 10 12 m −1 [135].…”
Section: Stability-antifouling Properties Of 2d Materials Nf Membranementioning
confidence: 99%